Regulatory challenges of innovation in food and agriculture market authorization requirements for new foods - van der Meulen, Bernd; Szajkowska, Anna (Applied Studies in Agribusiness and Commerce, 2012)
Regulatory authorities face the challenge to strike a fair balance between the interests of consumers to ensure the safety of innovative foods and agricultural products and the interest of innovative businesses.Worldwide prior authorization schemes are applied. This contribution explores characteristics, pros and cons of such schemes. It identifies concerns but also best practices that may contribute to improving food safety without unduly hampering innovation.